The role of the Siglec-G ITIM domain during bacterial infection - Wu, Yin; Yang, Darong; Chen, Guo-Yun (Cellular and Molecular Biology, 2022)
Siglecs, membrane-bound lectins of the sialic acid-binding immunoglobulin superfamily, inhibit immune responses by recruiting tyrosine phosphatases (e.g., SHP-1 and SHP-2) through their cytoplasmic immunoreceptor tyrosine-based inhibition motif (ITIM) domain. The role of Siglecs in infection has been extensively studied, but downstream signaling through the ITIM domain remains unclear. Here, we used a GST pull-down assay to identify additional proteins associated with the ITIM domain during bacterial infection. Gdi2 bound to ITIM under normal homeostasis, but Rab1a was recruited to ITIM during bacterial infection. Western blot analysis confirmed the presence of SHP-1 and SHP-2 in eluted ITIM-associated proteins under normal homeostasis. We confirmed the association of ITIM with Gdi2 or Rab1a by transfection of corresponding expression vectors in 293T cells followed by immunoprecipitation-western blot assay. Thus, ITIM’s role in the inhibition of the immune response during bacterial infection may be regulated by interaction with Gdi2 and Rab1a in addition to SHP-1 and SHP-2.